Live-attenuated CHIKV vaccine with rearranged genome replicates in vitro and induces immune response in mice. - Irina Tretyakova; Joongho Joh; Mary Gearon; Jennifer Kraenzle; Sidney Goedeker; Ava Pignataro; Brian Alejandro; Igor S Lukashevich; Donghoon Chung; Peter Pushko (Public Library of Science (PLoS), 2024)
Chikungunya fever virus (CHIKV) is a mosquito-borne alphavirus that causes wide-spread human infections and epidemics in Asia, Africa and recently, in the Americas. CHIKV is considered a priority pathogen by CEPI and WHO. Despite recent approval of a live-attenuated CHIKV vaccine, development of additional vaccines is warranted due to the worldwide outbreaks of CHIKV. Previously, we developed immunization DNA (iDNA) plasmid capable of launching live-attenuated CHIKV vaccine in vivo. Here we report the use of CHIKV iDNA plasmid to prepare a novel, live-attenuated CHIKV vaccine V5040 with rearranged RNA genome. In V5040, genomic RNA was rearranged to encode capsid gene downstream from the glycoprotein genes. Attenuated mutations derived from experimental CHIKV 181/25 vaccine were also engineered into E2 gene of V5040. The DNA copy of rearranged CHIKV genomic RNA with attenuated mutations was cloned into iDNA plasmid pMG5040 downstream from the CMV promoter. After transfection in vitro, pMG5040 launched replication of V5040 virus with rearranged genome and attenuating E2 mutations. Furthermore, V5040 virus was evaluated in experimental murine models for general safety and immunogenicity. Vaccination with V5040 virus subcutaneously resulted in elicitation of CHIKV-specific, virus-neutralizing antibodies. The results warrant further evaluation of V5040 virus with rearranged genome as a novel live-attenuated vaccine for CHIKV.